2007
DOI: 10.1007/s11745-007-3133-6
|View full text |Cite
|
Sign up to set email alerts
|

A Reliable Biomarker Derived from Plasmalogens to Evaluate Malignancy and Metastatic Capacity of Human Cancers

Abstract: Antigen tumor markers employed in monitoring therapeutical approaches are limited by their specificity (Sp) and sensitivity (Se). The aim of this study was to investigate the suitability of a lipid tumor marker derived from ether-linked phospholipids and to compare it with others usually assayed in clinical practice. Complex lipids from normal and pathological breast, lung, and prostate tissue were isolated and analyzed by TLC and c-GLC methods. Results were compared as pooled samples, or by means of the avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 34 publications
5
45
0
Order By: Relevance
“…Importantly, previous publications demonstrated that the analysis of lipid extracts obtained from tumor human cells lines or human cancer biopsies showed increased levels of PC and/or PE ether lipids. In fact, these changes are correlated with malignancy and metastatic potential in various cancers [37][38][39][40][41][42]. Some studies demonstrated that plasmalogens are natural antioxidants, as the ether link is more prone to be oxidized than the double bonds usually found in many phospholipids in their fatty acid moiety [9,43].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, previous publications demonstrated that the analysis of lipid extracts obtained from tumor human cells lines or human cancer biopsies showed increased levels of PC and/or PE ether lipids. In fact, these changes are correlated with malignancy and metastatic potential in various cancers [37][38][39][40][41][42]. Some studies demonstrated that plasmalogens are natural antioxidants, as the ether link is more prone to be oxidized than the double bonds usually found in many phospholipids in their fatty acid moiety [9,43].…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence for the involvement of oxylipins (Poczobutt et al 2006) and phospholipid species (Tyurina et al 2011) in tumour development from animal models of lung cancer. This is supported by clinical studies showing altered profiles of various lipids in plasma of lung cancer patients, including lysophospholipids (Dong et al 2010;Guo et al 2012), free fatty acids (Liu et al 2014), sphingomyelins, plasmalogens, phosphoglycerides and related lipids (Smith et al 2008;De Castro et al 2008;Ma et al 2011). Lipid profiling or lipidomics is an emerging field within metabolomics which focuses on monitoring changes in biofluid profiles of lipids and factors that interact with lipids.…”
Section: Introductionmentioning
confidence: 84%
“…The lipid biomarkers which contributed most to differentiate between adenocarcinoma and squamous carcinoma were phospholipids, triglycerides and sphingomyelins (Table 4) Alzheimer's disease and metastatic cancer (Brites et al 2004, Smith et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Ether-linked GPLs affect membrane fl uidity and are associated with several cellular dysfunctions and malignancies. The presence of these lipid species is typically correlated to metastatic properties of human cancers ( 67 ) and may be involved in the intrahepatic metastasis of HCC.…”
Section: Discussionmentioning
confidence: 99%